The heritage of glatiramer acetate and its use in multiple sclerosis. Issue 1 (December 2016) - Comi, Giancarlo; Amato, Maria; Bertolotto, Antonio; Centonze, Diego; De Stefano, Nicola; Farina, Cinthia; Gallo, Paolo; Ghezzi, Angelo; Grimaldi, Luigi; Mancardi, Gianluigi; Marrosu, Maria; Montanari, Enrico; et al.
Abstract Multiple sclerosis (MS) is a chronic and progressively debilitating disease of the central nervous system. Treatment of MS involves disease-modifying therapies (DMTs) to reduce the incidence of relapses and prevent disease progression. Glatiramer acetate (Copaxone®) was the first of the currently approved DMTs to be tested in human subjects, and it is still considered a standard choice for first-line treatment. The mechanism of action of glatiramer acetate appears to be relatively complex and has not been completely elucidated, but it is likely that it involves both immunomodulating and neuroprotective properties. The efficacy of glatiramer acetate 20 mg/mL once daily as first-line treatment in relapsing-remitting MS is well established, with ample evidence of efficacy from both placebo-controlled and active-comparator controlled clinical trials as well as real-world studies. There is also a considerable body of evidence indicating that the efficacy of glatiramer acetate is maintained in the long term. Clinical trial and real-world data have also consistently shown glatiramer acetate to be safe and well tolerated. Notably, glatiramer acetate has a good safety profile in women planning a pregnancy, and is not associated with foetal toxicity. Until recently, glatiramer acetate was only approved as 20 mg/mL once daily, but a new formulation with less frequent administration, 40 mg/mL three times weekly, has been developed and is now approved in many countries, including Italy. This review examines the mechanism of action, clinical efficacy, safety and tolerability of glatiramer acetate to provide suggestions for optimizing the use of this drug in the current MS therapeutic scenario.